A Review on Wind Induced Fatigue Analysis for High-Mast Lighting Towers - Jeyamohan, K.; Bandara, C.S.; Jayasinghe, J.A.S.C. (Young Members’ Conference 2021, Institution of Engineers, Sri Lanka, October 9, 2021/ ISBN 978-624-5810-02-4, 2021)
Recent developments on high-mast arm structures have increased awareness of the fatigue behavior associated with these structures. Mast arm structures that are subjected to cyclic loading conditions tend to fail due to fatigue failure. Size and thickness of base plate, geometry and thickness of mast arm, welding thickness and numbers of anchor bolts are highly influencing on the fatigue performance of a high-mast lighting tower system. It was found that, dynamic characteristics and damping ratio of the mast arm also has the most significant effect on the hotspot stress of the mass arm wall system. Palmgren Miner theory of cumulative damage method, Weibull wind distribution and S-N Curves are widely used to estimate the fatigue life of the structures. Since, there are no redundancy built into this high-mast arm structures, failure of these structures would be very hazardous. Generally, failures are observed around the man access hole, base connection and anchor bolt location due to high stress concentration at these locations. Furthermore, lock-in conditions in the second mode must be investigated as this mode is more critical for bending response. So, fatigue study of high-mast arm structures should be performed against excessive stress developed due to resonant vibration of periodic or random oscillation depending upon the flow regime.
Keywords: Hotspot; High- mast arm; Damage; Fatigue